I will not ever never eat a tomato : featuring Charlie and Lola - Child, Lauren 1965- (London : Orchard books, 2015)
Charlie tries to persuade her sister Lola of the advantages of eating healthily.
Originally published: 2000
Keywords: Tomate; Bilderbuch; Verweigerung; Nahrungsaufnahme; Food habits; Pictorial works; Juvenile fiction; Children's stories; Pictorial works